2017
DOI: 10.1038/s41598-017-08568-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum homocysteine levels and anxiety and depression among children and adolescents in Taiwan

Abstract: Although evidence suggests that homocysteine levels are elevated in severe mental illness in children, findings regarding homocysteine levels in youth with anxiety and depression are scarce. Therefore, this study examined the association of homocysteine levels with anxiety and depression in a community sample of students aged 6–13 years. In total, 649 students were selected from the first, fourth, and seventh grades of schools in Taipei, Taiwan, in 2010. These students completed a hospital-based health examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 25 publications
3
24
3
1
Order By: Relevance
“… 45 Besides, deficiency of magnesium can lead to dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis and anxiety. 50 Depression is associated with oxidative stress, 13 inflammation, 12 the high level of homocysteine, 51 scarcity of neurotransmitter serotonin 52 or catecholamine, 53 neurodevelopment disruptions, 54 and abnormal HPA axis. 55 Therefore, sufficient carotenoids, 56 flavonoids, 25 vitamin C, 49 vitamin B2, 57 folate, 58 and magnesium 33 may have anti-depression effects.…”
Section: Discussionmentioning
confidence: 99%
“… 45 Besides, deficiency of magnesium can lead to dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis and anxiety. 50 Depression is associated with oxidative stress, 13 inflammation, 12 the high level of homocysteine, 51 scarcity of neurotransmitter serotonin 52 or catecholamine, 53 neurodevelopment disruptions, 54 and abnormal HPA axis. 55 Therefore, sufficient carotenoids, 56 flavonoids, 25 vitamin C, 49 vitamin B2, 57 folate, 58 and magnesium 33 may have anti-depression effects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, hyperhomocysteinemia is reported to be affected by different dietary patterns [ 71 ]. Hyperhomocysteinemia has been related to anxiety-like behaviors in rats [ 72 ] and human [ 73 ]. On the other hand, low levels of homocysteine may induce epilepsy [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased HCy levels have been observed in depressed adolescents, compared to the controls [31]. Chung et al [32] found higher serum HCy levels in boys (12-13 years old) with moderate-to-high anxiety levels. However, no association was observed between serum HCy levels and depression in both boys and girls.…”
Section: Introductionmentioning
confidence: 92%